Comparative tests of tool steels used in machine work - Carlson, W. W.; Challender, R. T. (My University, 1908)
Introduction: In those branches of the engineering world which require tool steels in the manufacture of their products, there is probably no question of greater importance than that of procuring steels that will produce the results sought in the quickest, cheapest, possible way.
Citation: Carlson, W. W. and Challender, R. T. Comparative tests of tool steels used in machine work. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Engineering; Tools; Manufacturing; Graduating theses; Senior theses; Theses